Occupier’s liability: duty of occupier of land to trespasser / Zulkharnain Hashim - Hashim, Zulkharnain (Faculty of Law, 1986)
“Occupier” is simply a convenient word for a person who has a sufficient degree of control over promises to put him under a duty of care towards those who law full, onto the premises. A degree of control is prima facie sufficient if it is such that a defendant ought to realise that a failure on his part to use care may result in injury to a person coming on the premises. In this case the defendant need not have exclusive control.